Improving Hand Hygiene in a Rural Critical Access Hospital - Katherine Miller; Kathrine Jones; Rhonda Johnson; Jodie Becker (Rural Nurse Organization; Binghamton University, 2023)
Background: Hand hygiene adherence is the single most important infection control practice among healthcare workers. Hand hygiene is cost-effective and adherence to protocols can reduce hospital-acquired infections. Research regarding hand hygiene adherence has been shown to improve patient safety and reduce hospital-acquired infections. Adherence to hand hygiene protocols among healthcare workers is poor and improvement efforts lack sustainability. Purpose: The purpose of this project is to improve hand hygiene to be at or greater than 90% in acute care areas of a critical access hospital. Target population: The target population includes clinical and non-clinical staff working in a 7-bed emergency department and a 24-bed acute medical-surgical unit of a rural critical care hospital in North Carolina. Method: The Model for Improvement was used to guide the aims, measures, and change. Process improvement was conducted using Plan-Do-Study-Act (PDSA) test cycles method. Findings: Two acute care units were monitored for 3 months during which interventions occurred over two PDSA cycles. One unit showed steady improvement each month but did not meet its goal. The other unit exceeded goal metrics in the first and third months of the monitoring period. Conclusions: Surveys, verbal reminders, and interventions created discussions and greater awareness of hand hygiene. Keywords: hand washing, compliance, adherence, rural, critical access DOI:  https://doi.org/10.14574/ojrnhc.v23i1.736